PENDAMPINGAN DALAM STRATEGI PEMASARAN PADA UMKM DI DESA KUALA SEMPANG - Risnawati, Risnawati; Ginola Tri Shindy; Anggia Sekar Putri; Octaviani, Octaviani; Nanda Putri; Novitri Rahmawati; Salsabila, Salsabila; Risa Febriyatna (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Marketing strategy is a measurable action intended to introduce company products to the wider community. A marketing strategy is a collection of business steps that have been combined at the level of product introduction to making consumers make purchases. The problem we encountered was related to marketing strategies that had not been implemented properly in Kuala Sempang Village. For this reason, we held "Marketing Strategy Assistance for MSMEs in Kuala Sempang Village". The method we used when researching was using the direct assistance method. The results of the survey we conducted showed a lack of understanding regarding MSME marketing strategies in Kuala Sempang Village. So, it can be concluded that this marketing strategy assistance is very important for business actors, because having a marketing strategy can increase the sales targets they want to achieve.